Gaia 18dvy: a new FUor in the Cygnus OB3 association - Szegedi-Elek, Elza; Hundertmark, Markus; Tsapras, Yiannis (The astrophysical journal, 2020)
We present optical-infrared photometric and spectroscopic observations of Gaia 18dvy, located in the Cygnus OB3 association at a distance of 1.88 kpc. Gaia 18dvy was noted by the Gaia alerts system when its light curve exhibited a ≳4 mag rise in 2018-2019. The brightening was also observable at mid-infared wavelengths. The infrared colors of Gaia 18dvy became bluer as the outburst progressed. Its optical and near-infrared spectroscopic characteristics in the outburst phase are consistent with those of bona fide FU Orionis-type young eruptive stars. The progenitor of the outburst is probably a low-mass K-type star with an optical extinction of ∼3 mag. A radiative transfer modeling of the circumstellar structure, based on the quiescent spectral energy distribution, indicates a disk with a mass of 4 × 10−3 M ⊙. Our simple accretion disk modeling implies that the accretion rate had been exponentially increasing for more than 3 yr until mid-2019, when it reached a peak value of 6.9 × 10−6 M ⊙ yr−1. In many respects, Gaia 18dvy is similar to the FU Ori-type object HBC 722.
Gesehen am 29.09.2020